A case study approach for the effective design of a specialty bookstore - Manzo, Melissa Ann T.; Florendo Raquel Baltazar (2008.)
This case study focused on the effective design of a specialty bookstore. The purpose of the study was to identify the effective design components or features of the OMF Literature Bookstore, a company that publish, import, market books and other related merchandise that are Christ-centered. The design components were composed of the store layout, book displays, lighting design, color scheme, and interior signages. The study was designed as descriptive research which included multi-method research techniques of survey, interview and observation. OMF Literature Bookstore was selected as subject locale of the case study. A purposive sample was used in the study. The following criteria for the choice of the respondents include the following: customers present during the ocular visits of the researcher, customers under the age of 15 to 65 years old both male and female; and customers who visited the store at least twice a year. The sample size is limited to thirty (30) respondents due to time constraints experienced in data gathering. The researcher also interviewed staff of the store as well as observed the store interior for additional information. Responses of customers from the survey method were tallied, coded and categorized. The results were summarized in the form of frequencies which were reflected using bar graphs to indicate percentage tallies. The results concur with the determinants identified by the other studies mentioned in the literature review; which state that an effective bookstore design for a specialty bookstore focuses on the significance of the presence of book displays in a focal area. The inquiry results gathered from the survey also indicate this postulation. Customers ranked this as the most effective component. Ocular observation done by the researcher also agrees with the tabulated data of customer's responses.Tallied results also indicate that customers averagely visit the bookstore once a month and stayed inside the store premises an hour in a day. Aside from shopping books, other activities of customers inside the bookstore are to read books, to spend extra time as well as relax inside the store and, to meet someone like friends, family, relatives, etc. inside the bookstore. The analysis of data was based on customers ratings and ocular observation done by the researcher. The most effective design component is the book displays as determined by the data gathered. The store layout and signages respectively, were ranked accordingly as the second and third most important design components. The color of interior and the lighting used assumed a less significant position among the components identified. It was observed that, some of the design components of the bookstore such as signages and store layout; specifically their circulation clearances and quality of seating areas; required improvement. These aspects need to be modified to better suit the needs of the customers of the OMF Literature Bookstore. Several design recommendations were raised by the researcher in order to improve the current condition of the bookstore. These include the following aspects: the provision for comfortable seating spaces, the use of bigger signages and the rearrangement of the space to provide enough clearance between aisles in order to depart from the normal grid layout.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Specialty stores -- Philippines -- Designs and plans